Estudo das propriedades vibracionais e estruturais dos cristais monocloridrato de L-lisina dihidratada e monocloridrato de DL-lisina - Batista, José Cardoso (2016)
Crystals of L-lysine dihydrate monohydrochloride (L-lysine.HCl.2H2O) and DL-lysine monohydrochloride crystals (DL-lysine.HCl) were grown and their crystaline structures were confirmed by x-ray diffraction experiments and Rietveld's refinements. Raman spectroscopy experiments were performed as a function of temperature from 25 up to 115 ° C for the L-lysine. HCl.2H2O crystal. It was found that this crystal exhibits a phase transition at 55 ° C. The phase transition was identified by changes in Raman spectra in the spectral range from 35 to 3600 cm-1 . The transition was confirmed by X-ray diffraction experiments and thermal analysis. While no phase transition caused by temperature variation in the range of -193 to 127 ° C was observed through infrared spectroscopy and X-ray diffraction experiments for DL-lysine.HCl crystal. This crystal was also studied by Raman spectroscopy under high pressures up to 9.8 GPa, where the spectra in the range of 40 to 1200 cm-1 presented changes between 2.2 and 4.0 GPa that were associated with phase transition. Under decompression this transition proved to be reversible.